Weekend at Bernie's [videorecording (Blu-Ray)] - McCarthy, Andrew, 1962-; Silverman, Jonathan, 1966-; Stewart, Catherine Mary; Kiser, Terry; Klane, Robert, 1941-2023; Drai, Victor, 1947-; Kotcheff, Ted, 1931-2025 (MGM, 2014)
Two employees discover an embezzlement scam. The boss invites them to spend the weekend, with the intention of killing them. When the boys arrive, they find their boss dead, their lives in danger, and the prospects for a still-terrific weekend.